The Utilization of Papaya Leaf Infusion (Carica papaya) as a Natural Anesthetic for Rock Lobster (Panulirus penicillatus) - Yanti, Riska Dwi; Ukhty, Nabila (Universitas Teuku Umar, 2024)
The sale of lobster plays a significant role in the fisheries sector, particularly within the export market. Lobster transportation is typically carried out using a dry transport system. Anesthesia is a crucial step in the dry transport process. Anesthetic agents can be derived from natural sources, such as papaya leaf infusion. The aim of this study is to evaluate the effect of papaya leaf infusion on induction time and sedation time as a natural anesthetic for rock lobsters, as well as to determine the optimal concentration of papaya leaf infusion for use as a natural anesthetic. This research utilized an experimental design with three treatments: P1 (100 g/L), P2 (150 g/L), and P3 (200 g/L). The data collected included induction time, sedation time, and the survival rate of lobsters during the recovery period. The data were analyzed using descriptive and inferential statistical methods, including ANOVA and the Honest Significant Difference (HSD) test. The results indicated that varying concentrations significantly affected (P<0.05) induction time but did not significantly affect (P>0.05) sedation time. The induction time for treatments P1 and P2 was significantly different from that of P3. The survival rates were 100% for treatments P1 and P2, while P3 had a survival rate of 77.77%. The optimal concentration of papaya leaf infusion was found to be P1, which induced anesthesia in the lobsters within 50 minutes and 16 seconds, with a recovery time of 2 minutes, and a 100% survival rate